Climate change adaptation by federal agencies : plans, efforts, and issues. - Peterson, David (Climate change and its causes, effects, and prediction series., 2015)
Though Congress has debated the significance of global climate change and what federal policies, if any, should address them, the Government Accountability Office (GAO) since 2013 has identified the changing climate as one of the 30 most significant risks facing the federal government. President Obama established adaptation as a prominent part of his Climate Action Plan in June 2013. The November 2013 Executive Order 13653, Preparing the United States for the Impacts of Climate Change, directed agencies to undertake vulnerability assessments and planning for adaptation. The Administration aime.